The Nexus of Sustainability Practices and Financial Performance in the Islamic Banking Industry of Malaysia: The Moderating Role of Islamic Corporate Governance - Jan, Amin (2021)
The world is frequently facing drastic economic, environmental and social challenges of great impact due to the inefficient sustainability practices of firms